Anteseden Dan Konsekuensi Audit Delay Pada Perusahaan Perbankan Perioda 2011-2014 - Ronald Tehupuring; Theresia Febiengry Sitanala (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2016)
Timeliness in financial reporting can contribute to efficient performance for the stock market because it can reduce the asymmetry information, mitigate insider trading, and improve the usefulness decision of information to stakeholders. There were inconsistencies in prior research and the case of delay submission on issuer financial statements to the Financial Service Authority. There were 30 cases for each in 2013 and 2014. This study aimed to examine (1) the negative impact between the company size, profitability, leverage, and the auditor quality on audit delay; (2) the positive impact of audit delay on audit switching; and (3) the positive impact of audit delay and audit delay switching on audit quality in banking companies listed on the Stock Exchange 2011-2014 period. A purposive sampling method is used and as the sample, 30 companies are obtained in four years so the analyzed data was based on 120 observations. The data analysis technique used is multiple linear and logistic regression. Results showed that (1) the size of the company and leverage have no impact on audit delay, while the return on assets and the auditor quality have a negative impact and significantly related to audit delay; (2) audit delay has a positive impact and significantly related to audit switching; (3) audit delay has a positive impact and significantly related to audit quality, while audit switching has no impact on audit quality. This study has contributed in optimizing timeliness performance of financial information reporting, effectiveness and efficiency of audit time range so that general information increased, and The implication for audit quality of financial statements become more reliable.